Development of Beef Cattle Farmer Group of Suratthani Province for Response to Supply Chain - Pimpa, Opart; Tipmontean, Bunterng; Youngyai, Nattaya; Pimpa, Benchamaporn (Area Based Development Research Journal, 2019)
The project for development of beef cattle farmers group in Surat Thani province aims to solve farmers’ problems related to their strength, beef production efficiency, and marketing. A total of 632 farmers from 16 districts of Surat Thani join the project. Before operation, most farmers had problems with high feed cost, labor shortage, and unclear marketing strategies. Therefore, the current study has implemented change process in various aspects. They include arranging meetings to help set up a provincial beef cattle club, taking farmers for study visits in other provinces, organizing a beef cattle contest, providing training courses for research knowledge transfer, and settling marketing deals with big cooperatives. After five years of data collection (2008-2012), improvements in local farming efficiency and marketing are revealed. The value of beef cattle has increased by 20%. The farmers have developed their cattle breeding as the number of European crossbred cattle has increased by 80%. The feed costs are reduced by 35%. The cattle’s average growth rate is 0.8-0.95 kg/day, which increases from the original growth rate of 0.5-0.6 kg/day. Promotion of meat consumption by selling meat and food made from beef results in a 40% increase in the value of beef cattle. The research has encouraged the farmers to rely more on themselves and their groups. The project results are also used and extended to support the development of beef cattle farmer network in the southern provinces group on the Gulf of Thailand, whose purpose is to create a network of Srivijaya beef cattle farmers. The group receives continual support from the development budget for the southern provinces group on the Gulf of Thailand in 2013, 2014 and 2016. In the policy-oriented approach, the development of beef cattle in the southern region has been included in the National Economic and Social Development plan, Issue 12 on page 177. Such movements will benefit cattle farming and affect the long-term sustainability of beef farming in the southern region.